Hematological and biochemical evaluation of β-thalassemia major (βTM) patients in Gaza Strip: A cross-sectional study - Ayyash, Hani; Sirdah, Mahmoud (International Journal of Health Sciences, 2018)
Objectives: In Gaza Strip, Palestine, β-thalassemia is a major public health problem where more than 300 β-thalassemia major (βTM) patients are currently being managed at governmental hospitals. We set up to evaluate the hematological and biochemical aspects of our βTM patients at the Gaza European hospital and their correlation with iron overload. Methods: Our study included 65 transfusion-dependent βTM, as well as 37 apparently healthy subjects as control group. The hematological and biochemical evaluations included complete blood count, coagulation profile liver and kidney function tests, fasting blood sugar, lipid profile, and serum ferritin. Results: Deteriorated hematological and biochemical statuses were reported in both males and females of βTM patients as compared to the control group. Statistical comparisons showed no significant differences between males and females βTM patients in all parameters except for total cholesterol. The results concerning the splenectomized versus non-splenectomized patients revealed significantly higher values in splenectomized patients for white blood cell (WBC), platelet, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, albumin, total protein, cholesterol, and potassium concentration compared to the non-splenectomized patients. Patients infected with hepatitis C virus and/or hepatitis B virus showed significant decrease in WBC count as compared to infection free patients, while for serum urea and creatinine, the virally infected βTM patients revealed significantly higher values compared to infection free patients. Conclusion: This study justified the necessity for strengthening the efforts for regular evaluation and follow-up of the βTM patients which could be used to improve or modify the management protocols and thus ameliorating their deteriorated hematological and biochemical status.